[6, 6]‐Open and [6, 6]‐Closed Isomers of C70(CF2): Synthesis, Electrochemical and Quantum Chemical Investigation. Issue 52 (18th November 2013) - Samoylova, Nataliya A.; Belov, Nikita M.; Brotsman, Victor A.; Ioffe, Ilya N.; Lukonina, Natalia S.; Markov, Vitaliy Yu.; Ruff, Adrian; Rybalchenko, Alexey V.; Schuler, Paul; Semivrazhskaya, Olesya O.; Speiser, Bernd; Troyanov, Sergey I.; et al.
Abstract Novel difluoromethylenated [70]fullerene derivatives, C70(CF2)n (n=1–3), were obtained by the reaction of C70 with sodium difluorochloroacetate. Two major products, isomeric C70(CF2) mono‐adducts with [6, 6]‐open and [6, 6]‐closed configurations, were isolated and their homofullerene and methanofullerene structures were reliably determined by a variety of methods that included X‐ray analysis and high‐level spectroscopic techniques. The [6, 6]‐open isomer of C70(CF2) constitutes the first homofullerene example of a non‐hetero [70]fullerene derivative in which functionalisation involves the most reactive bond in the polar region of the cage. Voltammetric estimation of the electron affinity of the C70(CF2) isomers showed that it is substantially higher for the [6, 6]‐open isomer (the 70‐electron π‐conjugated system is retained) than the [6, 6]‐closed form, the latter being similar to the electron affinity of pristine C70. In situ ESR spectroelectrochemical investigation of the C70(CF2) radical anions and DFT calculations of the hyperfine coupling constants provide evidence for the first example of an inter‐conversion between the [6, 6]‐closed and [6, 6]‐open forms of a cage‐modified fullerene driven by an electrochemical one‐electron transfer. Thus, [6, 6]‐closed C70(CF2) constitutes an interesting example of a redox‐switchable fullerene derivative.